Corrosion Behavior of Diffusion Bonding Joints of (OFHC) Copper with Stainless Steel 304L in 3.5% NaCl - Ajeel, Sami Abualnoun; Akbar, Ahmed Ali Akbar; Hassoni, Safaa Mohammed (Al-Nahrain Journal for Engineering Sciences, 2018)
The present work deals with direct diffusion bonding welding without interlayer of austenitic stainless steel type AISI 304L with Oxygen Free High Conductivity pure copper (OFHC) in vacuum atmosphere (1.5 *10-5 mbr.). The optimum bonding conditions are temperature of 650 ?C, duration time of 45 min. and the applied stress of 30 MPa, in order to secure a tight contact between the mating surfaces. The corrosion behavior of diffusion bonding joints in 3.5% Nacl is studied to evaluate the corrosion resistance of welding joints by using Potentiodynamic method. The observed microstructure of corroded specimen of optimum diffusion bonding joint shows that the corrosion current density has low value as compared with base materials used. During polarization, galvanic coupling is observed between two materials used. At passivity region, inverse polarity is occurred at 450mV. Therefore, passive stainless steel 304 L behaves as cathode respective to pure copper, the corrosion behavior of the diffusion bonding joint was mostly by copper side. The corrosion results indicate the presence of galvanic effect. The corrosion current density of copper, stainless steel 304L and bond joints condition were (3.66 µA/cm2, 1.62 µA/cm2 and 1.85µA/cm2) respectively. A SEM examination of corroded diffusion bonding joint indicates that the galvanic corrosion happened on copper side. The corrosion rate of bonding joint conditions was 0.85 mpy, which is less than 1%. This means that corrosion resistance of bond joint is more than excellent.